BIOCHEMICAL COMPOSITION AND VARIATION OBTAINED IN THE LINSEED CAKES OF IMPORTANT GENOTYPES OR STRAINS - VIJAYA TRIPATHI; A. B. ABIDI (International Journal of Pharma and Bio Sciences, 2014)
Three different colour varieties of linseed have been studied for a comparative data analysis, results of this study provides valuable information regarding the fifty genotypes of linseed seeds which were grown in Department of Genetics and Plant Breeding. Department farm of SHIATS in year 2011-2012. The seeds were collected and brought into the biochemistry laboratories for biochemical investigation. The fifty genotypes were divided into three different colours, which was fawn, yellow and brown seeded varieties. The oil was extracted from fifty different varieties/strains of linseed seeded coloured varieties. Various biochemical parameters were analyzed in these studies that are percentage of oil content. The cake content was analyzed for protein, lysine, tryptophan, methionine and total ash by using standard methods. Among these three different colour linseed varieties fawn seeds contain the higher percentage of oil. Variation in biochemical constituents in three colour linseed varieties was observed in the range of 36.47-38.85% of oil. 31.69-36.21% for protein, 1.14-1.17% for Lysine, 0.43-0.48% for Tryptophan, 0.27-0.29% for Methionine, 5.76-5.94% for Ash content. The result indicates among the linseed three colour varieties yellow seeds varieties gave better performance as compare to the other genotypes of fawn and brown ones. Therefore, proximate biochemical composition of varieties helps to assess its nutritional and edible value in terms energy units compared to other varieties of linseed seeds.